The Messengers - Davis, Richard Harding, 1864-1916 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Messengers" by Richard Harding Davis is a romantic novella set in the early 20th century. The story revolves around the character Ainsley, who retreats to his isolated farm, Lone Lake Farm, in Connecticut, seeking solitude and a test of true friendship. He is deeply in love with Polly Kirkland and believes that her willingness to visit him in his secluded setting will determine the depth of their relationship. The narrative explores themes of love, longing, and the quest for genuine connection against a backdrop of nature. The plot follows Ainsley as he grapples with his emotions and the uncertainty of Polly$1 (Bs feelings while she travels abroad. As Ainsley waits for a sign to indicate her love for him, he becomes increasingly despondent with life and is haunted by his unrequited love. After months of waiting, he experiences a series of false alarms that rekindle his hope. Ultimately, just as he prepares to confront his feelings and doubts, a dramatic twist occurs when Polly reveals she never intended to send him a sign at all. Instead, his act of following her to Egypt is the manifestation of true love, illuminating that the most important messages are often understood through action rather than symbols. The novella culminates in a poignant and heartwarming reunion under the mysterious return of white birds, symbolizing the culmination of his longing and the realization of their love. (This is an automatically generated summary.)s
Release date is 2006-05-12
Produced by Don Lainson; David Widger
Keywords: Fiction; Short stories